Motors of Change for R&D and Innovation towards Sustainable Energy in Turkey - Kılkış, Şiir (Industrija, 2014)
There is a revival of mission-oriented R&D and innovation programs in prioritized areas that serve the aim of decoupling economic growth from environmental pressures. This paper analyzes the governance process in activating the innovation actors in the area of energy technologies in Turkey. This process that was coordinated by TÜBİTAK led to the National Energy R&D and Innovation Strategy for 2011-2016. The three main phases of this process are mapped to be strategy-building, prioritization, and implementation involving six different participatory approaches. The Strategy is based on the strategic aims of mission-oriented R&D projects, capacity advancement, commercialization, and governance. Two new, call-based grant programs launched with eleven energy calls in the first year are overviewed. These programs were key to activating a phase known as “motors of change” for the innovation system. The second year led to the selection of the topic of “Energy Efficiency” for a pilot technology roadmap process, which involved a separate, multi-actor governance process. The paper concludes with the key role of R&D and innovation in allowing energy to contribute to the sustainable development of Turkey by utilizing energy resources effectively and efficiently.